2013
DOI: 10.1590/0102-311x00070112
|View full text |Cite
|
Sign up to set email alerts
|

Um modelo bayesiano para investigação de sobremortalidade durante epidemia de dengue na Região Metropolitana do Rio de Janeiro, Brasil, 2007-2008

Abstract: O objetivo deste estudo é investigar a ocorrência de sobremortalidade durante a epidemia de dengue ocorrida na Região Metropolitana do Rio de Janeiro, Brasil, entre 2007 e 2008. Para obter a predição dos óbitos desses anos epidêmicos, um modelo dinâmico Poisson foi ajustado aos dados de mortalidade por dengue e por doenças que fazem parte do seu diagnóstico diferencial. Toda a inferência foi realizada sob o paradigma bayesiano. Verificou-se um excesso de mortalidade em março de 2008, em menores de 15 anos de i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…This was possibly mediated by the number of circulating serotype-susceptible people [ 29 , 30 ]. In Rio de Janeiro State in 2008, the dengue case incidence peak occurred during March and April3 [ 31 ], similar to the peak observed in Itaboraí.…”
Section: Discussionmentioning
confidence: 72%
“…This was possibly mediated by the number of circulating serotype-susceptible people [ 29 , 30 ]. In Rio de Janeiro State in 2008, the dengue case incidence peak occurred during March and April3 [ 31 ], similar to the peak observed in Itaboraí.…”
Section: Discussionmentioning
confidence: 72%
“…2009 ). The epidemic reached its peak in March and April, with 86,036 and 90,945 human cases reported, respectively, and had ended by June ( Malhão et al 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Field - All dengue-positive female Ae. aegypti were collected from March to early June 2008, corresponding to epidemic period reported by the Ministry of Health ( Malhão et al 2013 ). We analysed wing lengths of female Ae.…”
Section: Methodsmentioning
confidence: 99%
“…The epidemic period and change in the age profile, with an increase in the number of cases in children, presenting a disease whose clinical management was not common among pediatricians, may have contributed to this high case-fatality rate. Another study found these same factors, in addition to greater vulnerability in infants, as possible causes for this high death rate [16, 33].…”
Section: Discussionmentioning
confidence: 99%